STUDENT VOICES: EXPLORING LEARNERS' PERCEPTIONS OF QUESTION GAMES TO IMPROVE SPEAKING SKILLS IN AN INDONESIAN EFL CLASSROOM - Fiqhi Yulianingsih; Syarifuddin Dollah; Fatimah Hidayahni Amin (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This study investigated Grade VIII learners’ perceptions of using question games to improve speaking skills in an Indonesian EFL classroom. Employing a qualitative case study design, the research drew on classroom observations, four focus group discussions, reflective journal entries, and a students’ perception questionnaire (data collection conducted over four weeks) to capture both collective and individual experiences. Thematic analysis revealed consistently positive learner responses: students reported heightened enjoyment and motivation, increased confidence in speaking, greater incidental vocabulary acquisition, and a clear preference for small-group game formats that lowered affective barriers to participation. Quantitative summary data from the questionnaire corroborated these themes. Pedagogically, the findings indicate that question games can create low-pressure, interaction-rich opportunities that support fluency and willingness to communicate, provided they are complemented by teacher scaffolding and vocabulary reinforcement. Limitations include the single-class setting and short intervention period; future research should employ longitudinal designs, larger and more varied samples, and objective measures of speaking gains to triangulate perceptual evidence.